Sumber Daya Manusia dan Manusi Bersumber Daya dalam Organisasi - Peter . (Jurnal Manajemen Maranatha, 2007)
Orientation of business is not only making profit, but adding value to another. The relation between organization and human is a habitat to growing up human potential ability. Every people will fill different effect if changing is happen in their work place, the reaction from every people will different too, for example: resistance for new regulation or situation, worker always want to stay in the previous situation which make they comfortable. Empowerment for worker will make different situation, because worker will fill the attention from the management level. Learning for changing adaptation started from knowledge acquisition and insight, than habit and skill learning and emotional condition and learned anxiety.